Workshop communication: genomic sciences and Original people’s knowledge (Chubut Province, Argentina) - Tamburrini, Camila; Romero Saihueque, Rubén Ricardo; Dahinten, Silvia Lucrecia; Parolin, María Laura (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
On July 2, 2022, the first exchange meeting between genomic sciences and indigenous knowledge was held in Trelew, Chubut, Argentina. This event was carried out within the framework of an agreement between IDEAus-CONICET and the Directorate of Indigenous Affairs of the province that seeks to establish a genetic science that is aligned with the ethical standards of scientific work in relation to ancestral Indigenous communities and their descendants. The workshop included presentations and round table discussions on genetic studies in cosmopolitan and ancestral populations based on the study of archaeological remains stored in the Bioanthropological Repository at IDEAus-CONICET. An anonymous survey was carried out to know the participants’ perception of genetic sciences, the terms with which they recognize themselves and the forms and frequency of dissemination of scientific advances, among other points investigated. The analysis of this first workshop showed, amongst other findings, that there are failures in scientific communication and that the interest of the Indigenous communities in these meetings is closely linked to the struggle for the vindication and recognition of these communities. The importance of disseminating this information in the educational sphere from a decolonized perspective was highlighted.